Tapered optical fiber DNA biosensor for detecting Leptospira DNA - Jia-Yong Lam; Mohd Hanif Yaacob; Hui-Yee Chee (Asian Pacific Journal of Tropical Medicine, 2023)
Objective: To establish a DNA detection platform based on a tapered optical fiber to detect Leptospira DNA by targeting the leptospiral secY gene. Methods: The biosensor works on the principle of light propagating in the special geometry of the optical fiber tapered from a waist diameter of 125 to 12 µm. The fiber surface was functionalized through a cascade of chemical treatments and the immobilization of a DNA capture probe targeting the secY gene. The presence of the target DNA was determined from the wavelength shift in the optical transmission spectrum. Results: The biosensor demonstrated good sensitivity, detecting Leptospira DNA at 0.001 ng/µL, and was selective for Leptospira DNA without cross-reactivity with non-leptospiral microorganisms. The biosensor specifically detected DNA that was specifically amplified through the loop-mediated isothermal amplification approach. Conclusions: These findings warrant the potential of this platform to be developed as a novel alternative approach to diagnose leptospirosis.